The Role And Importance Of Extensive Mastering Of New Directions In The Visual Arts Through Art - Pedagogical Technology - Ilyasova Umida Azizovna (Genius Journals, 2025)
This article analyzes the role and importance and practical foundations of the broader mastering of new directions in the visual arts through art - pedagogical technology. The role of artistic and aesthetic education in the context of the reforms being implemented in the education system of Uzbekistan, the importance of modern technologies that serve to increase the effectiveness of the pedagogical process, as well as advanced foreign experiences are highlighted. The study substantiates the need to identify the personal capabilities of students, develop them and apply an individual, integrated approach to the educational process. The formation of aesthetic taste, compositional thinking and independent thinking skills through the visual arts is interpreted as a pedagogical goal
Keywords: fine arts; painting composition; creative potential; integrated approach